2017
DOI: 10.2147/mder.s107134
|View full text |Cite
|
Sign up to set email alerts
|

Risk management and regulations for lower limb medical exoskeletons: a review

Abstract: Gait disability is a major health care problem worldwide. Powered exoskeletons have recently emerged as devices that can enable users with gait disabilities to ambulate in an upright posture, and potentially bring other clinical benefits. In 2014, the US Food and Drug Administration approved marketing of the ReWalk™ Personal Exoskeleton as a class II medical device with special controls. Since then, Indego™ and Ekso™ have also received regulatory approval. With similar trends worldwide, this industry is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 51 publications
0
131
1
1
Order By: Relevance
“…Studies found that misalignment due to suboptimal fitting can increase the metabolic cost and discomfort of the wearer producing pain, injuries [56,57] and augment the risk of bone fractures [58,59]. Therefore, the structure of the exoskeleton has to be able to adapt to the anthropometry of the users [60].…”
Section: Design and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Studies found that misalignment due to suboptimal fitting can increase the metabolic cost and discomfort of the wearer producing pain, injuries [56,57] and augment the risk of bone fractures [58,59]. Therefore, the structure of the exoskeleton has to be able to adapt to the anthropometry of the users [60].…”
Section: Design and Structurementioning
confidence: 99%
“…Despite the fact that, in general, studies show that wearable exoskeletons are safe devices, these results may not be fully representative. According to He et al [58], studies tend to omit relevant details when reporting adverse events, differ on the inclusion/exclusion criteria, and do not report explicitly whether adverse events occurred. In the study by van Herpen et al [59], the authors reported the occurrence of two cases of bone fractures during training with exoskeleton and provided instructions for handling accidental situations such as an unexpected shut down of the control system of the exoskeleton.…”
Section: Safety and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Bone mineral density should be assessed before proceeding to training with robotic devices to avoid such accidents. 77 While adverse effects are transitory and mainly due to lack of individual adjustments, the beneficial effects of technologically assisted gait training can be seen even after one single session. For example, one session of training on TM with FES on dorsi and plantar flexors increases the peak of anterior ground reaction force and of integral ground reaction force in post-stroke users.…”
Section: Effects Of Using Technology For Gait Rehabilitationmentioning
confidence: 99%
“…In recent years, the lower-limb exoskeleton, or \wearable robot" as it is known, has substantially evolved and been an effective means to provide paraplegic and hemiplegic individuals with the ability to walk upright. [5][6][7][8][9][10][11][12] A lot of studies about the lower-limb exoskeletons have been developed to assist the impaired populations. Several commercial devices including Rewalk TM ; 13,14 Ekso TM ; 15,16 HAL r ; [17][18][19][20] and Indego TM ; [21][22][23][24][25] are on the market.…”
Section: Introductionmentioning
confidence: 99%